Synthesis, Characterization, and Theoretical Study of a New Organotellurium Ligands Containing Amino Group - Gofran Safi Mokhtar; Nuha Hussain Al-Saadawy (Universitas Gadjah Mada, 2023)
The aim of the current study is to prepare organomercury and organotellurium compounds containing amino groups such as [1,1'-biphenyl]-4-amine and their derivatives by a mercuriation reaction. The research includes the preparation of a new organotellurium compound based on [1,1'-biphenyl]-4-amine. C12H10NHgCl (A) was obtained by mercuriation reaction to [1,1'-biphenyl]-4-amine by mercuric acetate and lithium chloride. C12H10Br3NTe (B), C24H20N2Br2Te (C), C24H20N2Te (D), and C24H20N2Te2 (E) were prepared by different reactions to get the corresponding compounds. All the prepared ligands were characterized by using infrared spectroscopy and mass spectroscopy. DFT has been obtained by the basis set 3-21G to investigate the molecular structure of the new prepared organotellurium compounds. HOMO and LUMO surfaces, geometrical structure, and energy gap have been obtained throughout the geometry optimization. Finally, the electron affinity, electronegativity, electrophilicity, ionization potential, and lower case of organotellurium compounds have been calculated and discussed. The result of the chemical analysis showed that it agreed with the proposed chemical structures, and a theoretical study using DFT has concluded that more stability of the prepared organotellurium compounds.